A Comparative in Invitro Investigation of Aging Effects on Colour Stability and Fracture Toughness of 3D Printed Interim Restorations - Nahata, Bhavini; Shah, Khushali (Journal of Neonatal Surgery, 2025)
Advancements in digital dentistry have revolutionized the fabrication of interim restorations, with 3D printing technologies offering enhanced precision, efficiency, and customization. This study compares two prominent 3D printing methods—stereolithography (SLA) and digital light processing (DLP)—to evaluate their dimensional accuracy and color stability in the production of provisional dental restorations. Thirty samples were digitally designed using Exocad and printed using SLA and DLP technologies. Dimensional accuracy was assessed through high-resolution 3D scanning and best-fit alignment in Geomagic Control X software, while color stability was tested by immersing the restorations in turmeric and coffee solutions for seven days, followed by spectrophotometric analysis. Results indicated that both SLA and DLP produced restorations with comparable dimensional fidelity and color resistance, with no statistically significant differences. These findings suggest that both printing technologies are clinically reliable and can be chosen based on workflow needs without compromising restoration quality.